Penentuan Strategi Pemenuhan Permintaan dan Perbaikan Tata Letak Produk di Gudang (Studi Kasus Toko X) - Jessica Octaviani Rustandi; Kartika Suhada; Rainisa Maini Heryanto (Jurnal Rekayasa Sistem Industri, 2022)
Fulfillment customer demand is main factor that have to be considered by company to win competitive competition. Right strategy is needed to meet this objective and create minimum total inventory costs. During COVID-19 pandemic, hygiene products become products that have skyrocketing demand, thus encouraging emergence of new stores selling it. One of them is Store X that sells hygiene products. The problem is discrepancy between demand from consumers with quantity of coming products. Store X warehouse also has products that are not well organized, causing difficulties in retrieval and storage products. Currently, Store X used Optional Method to control inventory based on store policy, resulting in high holding costs. This research proposed 2 inventory control strategies, where in each strategies considering Q, P, and Optional Method, as well as selected the best method based on minimum inventory total costs. First strategy, store order all of products to supplier, if there is shortage will produce 50 jerrycans. Second strategy, store always produces 4 types of products using EPQ method, while the other will be order to supplier. Based on selected strategy, warehouse layout is proposed using Class-Based Dedicated Storage Policy. From the results, second strategy with Q method is selected, that results savings in holding costs and production costs, although increase in ordering costs and shortage costs. Total cost savings per 6 months IDR 3.716.543,35 or 60,79%. Application of proposed warehouse layout, all of products are well and neatly organized, so that could increase effectivity and efficiency in retrieval and allocation.